Transcriptome and Metabolome Dynamics Explain Aroma Differences between Green and Red Prickly Ash Fruit - Fei, Xitong (Foods, 2021)
Green prickly ash (Zanthoxylum armatum) and red prickly ash (Zanthoxylum bungeanum) fruit have unique flavor and aroma characteristics that affect consumers’ purchasing preferences. However, differences in aroma components and relevant biosynthesis genes have not been systematically investigated in green and red prickly ash. Here, through the analysis of differentially expressed genes (DEGs), differentially abundant metabolites, and terpenoid biosynthetic pathways, we characterize the different aroma components of green and red prickly ash fruits and identify key genes in the terpenoid biosynthetic pathway. Gas chromatography-mass spectrometry (GC-MS) was used to identify 41 terpenoids from green prickly ash and 61 terpenoids from red prickly ash. Piperitone was the most abundant terpenoid in green prickly ash fruit, whereas limonene was most abundant in red prickly ash. Intergroup correlation analysis and redundancy analysis showed that HDS2, MVK2, and MVD are key genes for terpenoid synthesis in green prickly ash, whereas FDPS2 and FDPS3 play an important role in the terpenoid synthesis of red prickly ash. In summary, differences in the composition and content of terpenoids are the main factors that cause differences in the aromas of green and red prickly ash, and these differences reflect contrasting expression patterns of terpenoid synthesis genes.